Romanticism in the Paraguayan War: Between the beautiful and the sublime in the work of the painter Edoardo de Martino - Albuquerque, Fernanda Deminicis de; Loureiro, Marcello José Gomes (Revista do Instituto Histórico e Geográfico Brasileiro, 2024)
The article focuses on the circulation of ideas and aesthetic patterns connected to the Romantic Movement, and aims to investigate the antinomies of civilization and barbarism in the work of the Italian painter Edoardo de Martino. The text assumes the need to include his works in a broader perspective in order to reveal new possibilities and forms of understanding his artistic production. Thus, the elements directly linked to the movement at issue such as raging seas, the moonlight, dreamlike landscapes and wars take on other meanings. As main sources for the study, we used concepts from the Kantian philosophy, Baudelaire’s writings, Conde d’Eu’s diary and, of course, some of De Martino ́s drawings and paintings, which we compared with those of other artists of his time. One of the conclusions reached is that, in addition to asserting the credibility of a nation- state capable of mobilizing itself for war and conducting it in a civilized manner, the images exalted the sacrifice of anonymous individuals for the nation. By doing so, they invited the spectators to be part of the nation building and civilization.